Highly efficient adsorption performance of a novel magnetic geopolymer/Fe3O4 composite towards removal of aqueous acid green 16 dye. Issue 3 (June 2020) - Rossatto, D.L.; Netto, M.S.; Jahn, S.L.; Mallmann, E.S.; Dotto, G.L.; Foletto, E.L.
Highlights: Magnetic geopolymer/Fe3 O4 composite was employed as a remarkable adsorbent. High adsorption capacity towards aqueous green 16 dye. Facile separation from the liquid solution by using a magnetic system. Abstract: A novel magnetic geopolymer/Fe3 O4 composite (MGP) was prepared from metakaolin, biogenic rice husk silica and magnetite (Fe3 O4 ), having as mesopores–structuring agents hydrogen peroxide and soybean oil. The magnetic property and mesoporosity were confirmed by vibrating sample magnetometer (VSM) and BET isotherms, respectively. An adsorption study of aqueous acid green 16 (AG16) dye onto composite was performed. The parameters adsorbent dosage and initial pH were evaluated by experimental design in order maximize the adsorption efficiency of AG16 dye onto MGP. Through the results, fast adsorption and an equilibrium reached at 30 min were observed. The kinetic data fitted well to the pseudo–second order model. Remarkable sorption capacity of 400 mg g –1 at 328 K was obtained. Additionally, the composite presented high reusability even after several repeated cycles, indicating that it can be a potential adsorbent towards removal of organic pollutants from liquid effluents.